BACKWASH EFFECTS OF PORTFOLIO ASSESSMENT IN ACADEMIC WRITING CLASSES - Muh Syafei (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
This paper discusses a study investigating studentsâ opinions and reflections on backwash effects of portfolio assessments applied in Academic Writing course. To obtain the data, the researcher carried out interviews with 70 students of English Education Department (EED) of Universitas Muria Kudus (UMK) who took Academic Writing I and II courses. A qualitative analysis was then administered by identifying and classifying contents of studentsâ opinions and reflections expressed in the studentsâ responses concerning the backwash effects of the portfolio assessment applied in the courses. This investigation concludes the followings. First, all the research subjects support the use of portfolio assessment in Academic Writing Classes. Second, portfolio assessment provides various positive backwash effects on the student learning. Third, the students consider the portfolio assessment a fairer assessment. These findings suggest that the students respond positively to the portfolio assessment. Thus, it is recommended that the application of portfolio assessment in academic writing classes be maintained.